Estratégias de avaliação da energia e digestibilidade dos alimentos para cães - Wandrea de Souza Mendes (2006)
A trial was conducted in the Animal Metabolism and Calorimetry Laboratory of the Vet School- UFMG to evaluate the efficacy of the indirect methods (LIPE®, Cr2O3 and tritiated water) in the determination of fecal and urinary production, the dry matter, crude protein, ether extract apparent digestibility and energetic values for ten dog pet foods. The trial was divided into two metabolic essays and respirometry, repeated by time. Five pet foods and five non-purebred adult male dogs were used, 17.6 ± 2.2 Kg b.w. in each step. It was used a simple trial design, with one animal by experimental unity. The methods were the treatments. The results of the indirect methods were compared to the direct methods results by pairment statistical method and analyzed by t test. The fecal dry matter, DM, CP, EE digestibilities and the DE values estimated by LIPE® and Cr2O3 did not show differences from values obtained by fecal total collection (p>0.05). The tritiated water underestimated the urinary production in average of 24.0% (p<0.05), but it did not cause differences in the ME values (p>0.05) due to low energy losses by the urine. The NE values estimated by indirect methods in the steps before the respirometry were similar (p>0.05) from the values obtained by the direct method. The markers demonstrated efficacy. The recovery rates were: LIPE® 99.5%; Cr2O3 105.5 % and tritiated water 90.3%.